2014
DOI: 10.1088/1009-0630/16/1/04
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Response to Supersonic Molecular Beam Injection in J-TEXT

Abstract: Recently, hydrogen fueling experiments with supersonic molecular beam injection (SMBI) system have been performed in the J-TEXT tokamak. To evaluate the effects of the injection amount of SMBI on plasma behaviors, moderate and intensive SMBs have been separately injected and compared with each other in Ohmic discharges. With moderate SMBs, electron density increases about twice as before, the size of magnetic island slightly decreases, and the edge toroidal rotation speed in a counter-current direction, measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Because SMBI has a higher fueling efficiency than GP under different regimes, it could assume the role of GP in fusion devices. Because of its good performance and further optimization in the future (Yao et al 2004(Yao et al , 2007Pegourie et al 2003;Zheng et al 2013;Lang et al 2005;Soukhanovskii et al 2004;Takenaga et al 2009;Kim et al 2013;Murakami et al 2012;Mizuuchi et al 2010;Xiao et al 2014aXiao et al , 2021Yao and Baldzuhn 1933;Tanna et al 2019;Islam et al 2016), SMBI might play a pivotal Fig. 11 Fueling efficiencies of the SMBI system and GP in different plasma discharge regimes (Yuan et al 2018) role under a variety of conditions for future fusion devices, such as the start-up phase and pellet-free injection of helium discharge.…”
Section: Smbi Fueling Efficiency In Different Confinement Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because SMBI has a higher fueling efficiency than GP under different regimes, it could assume the role of GP in fusion devices. Because of its good performance and further optimization in the future (Yao et al 2004(Yao et al , 2007Pegourie et al 2003;Zheng et al 2013;Lang et al 2005;Soukhanovskii et al 2004;Takenaga et al 2009;Kim et al 2013;Murakami et al 2012;Mizuuchi et al 2010;Xiao et al 2014aXiao et al , 2021Yao and Baldzuhn 1933;Tanna et al 2019;Islam et al 2016), SMBI might play a pivotal Fig. 11 Fueling efficiencies of the SMBI system and GP in different plasma discharge regimes (Yuan et al 2018) role under a variety of conditions for future fusion devices, such as the start-up phase and pellet-free injection of helium discharge.…”
Section: Smbi Fueling Efficiency In Different Confinement Regimesmentioning
confidence: 99%
“…Its high fueling efficiency was also demonstrated in several tokamaks, such as HL-2A (Yao et al 2007, Tore Supra (Pegourie et al 2003), and EAST (Zheng et al 2013). Thus, it has been widely implemented in many notable fusion research devices, such as ASDEX Upgrade (Lang et al 2005), NSTX (Soukhanovskii et al 2004), JT-60U (Takenaga et al 2009) KSTAR (Kim et al 2013), LHD (Murakami et al 2012), Heliotron J (Mizuuchi et al 2010), J-TEXT (Xiao et al 2014a), W7-AS (Yao and Baldzuhn 1933), ADITYA-U (Tanna et al 2019), andGAMMA 10 (Islam et al 2016). Owing to its flexibility and fast response, the SMBI technique has also been well developed for density feedback control on HL-2A and EAST (Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The SMBI excites magnetic islands, as long as the injected hydrogen quantity is above a certain threshold in J-TEXT [48]. Moreover, the RE loss increased rapidly if large TMs were excited [43].…”
Section: Suppression Of Res By Rmp and Smbimentioning
confidence: 99%
“…In J-TEXT, magnetic perturbations are excited by supersonic molecular beam injection (SMBI), when the injected hydrogen quantity is about 3.0×10 19 molecules [29]. It is found that the excited magnetic perturbations cause a prompt RE loss.…”
Section: Introductionmentioning
confidence: 99%